2021
DOI: 10.1111/cns.13638
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture facilitates the integration of a grafted TrkC‐modified mesenchymal stem cell‐derived neural network into transected spinal cord in rats via increasing neurotrophin‐3

Abstract: Aims This study was aimed to investigate whether electroacupuncture (EA) would increase the secretion of neurotrophin‐3 (NT‐3) from injured spinal cord tissue, and, if so, whether the increased NT‐3 would promote the survival, differentiation, and migration of grafted tyrosine kinase C (TrkC)‐modified mesenchymal stem cell (MSC)‐derived neural network cells. We next sought to determine if the latter would integrate with the host spinal cord neural circuit to improve the neurological function of injured spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Although these transdifferentiated cells are neuron‐like, they express most neuron markers including cytoskeleton proteins (neurofilament [NF]‐200, NF‐H, microtubule‐associated protein [MAP]2, and β‐tubulin III); synaptic structure proteins (postsynaptic density [PSD]‐95 and synaptophysin); neurotransmitters (γ‐aminobutyric acid [GABA] and choline acetyltransferase [ChAT]); and doublecortin (DCX). We have also shown that some of the TrkC gene‐modified MSC‐derived cells exhibit electrophysiologic properties in vitro, such as postsynaptic currents and action potentials in the presence of Schwann cells overexpressing NT‐3 93,95 . Importantly, the cells form extensive connections or contacts with host neurons and descending 5‐HT‐positive nerve fibers.…”
Section: Gv‐ea Alleviates Sci By Promoting the Integration Of Transpl...mentioning
confidence: 87%
See 2 more Smart Citations
“…Although these transdifferentiated cells are neuron‐like, they express most neuron markers including cytoskeleton proteins (neurofilament [NF]‐200, NF‐H, microtubule‐associated protein [MAP]2, and β‐tubulin III); synaptic structure proteins (postsynaptic density [PSD]‐95 and synaptophysin); neurotransmitters (γ‐aminobutyric acid [GABA] and choline acetyltransferase [ChAT]); and doublecortin (DCX). We have also shown that some of the TrkC gene‐modified MSC‐derived cells exhibit electrophysiologic properties in vitro, such as postsynaptic currents and action potentials in the presence of Schwann cells overexpressing NT‐3 93,95 . Importantly, the cells form extensive connections or contacts with host neurons and descending 5‐HT‐positive nerve fibers.…”
Section: Gv‐ea Alleviates Sci By Promoting the Integration Of Transpl...mentioning
confidence: 87%
“…Previous researches have showed that the MSC-derived neuron-like cells in the injury/graft site of spinal cord were integrated into the host neural circuitry; therefore, they can receive neural input from the rostral and caudal areas of the injury/graft site in the transected SC and transmit the information to host neurons on both sides of the gap (Figure 3). 3,93 As reported previously, the aim of the this particular strategy is to induce the transdifferentiation of TrkC gene-modified MSCs into neuron-like cells that can serve as a relay mechanism upon transplantation into a gap in the SC. [94][95][96] To sum up, these processes promoted the regeneration of SC tissue and improved motor function in paralyzed limbs.…”
Section: Gv-e Aalle Viate Ssciby Promotingtheinteg R Ati Onof Tr An S...mentioning
confidence: 90%
See 1 more Smart Citation
“…Co-transplantation of SCs with other cell types, including olfactory-ensheathing cells (Fouad et al, 2005), neural stem cells/progenitors (Niapour et al, 2012), and bone marrow mesenchymal stromal cells (MSC), can improve the repair of spinal cord injury because the cell types play complementary functions (Pourheydar et al, 2012). Interestingly, Ding et al transplanted SCs-MSC-derived neural network implant combined with EA in rats, which can accelerate neural network reconstruction and restoration of spinal cord function following SCI (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, acupuncture is applied regularly in neurological diseases and injuries including SCI [30]. Recent studies demonstrated that acupuncture induced rodent neuroregeneration after brain damage and an increase in the number of motor neurons accompanied by increased expression of glia-derived neurotrophic factor in the spinal cord [31,32] and facilitated the integration of a grafted neural network [33]. Obviously, electroacupuncture downregulates proapoptotic signals and upregulates antiapoptotic proteins like Bcl-2 [34].…”
Section: Acupuncture Decreases Serum Concentrations Of Bdnfmentioning
confidence: 99%